Characterization of the Volatile Profiles of Six Industrial Hemp (Cannabis sativa L.) Cultivars - Sofkova-Bobcheva S (American Society of Agronomy)
Volatile organic compounds (VOCs) play an important role in plant ecology and can be useful in pest management. This work characterises, for the first time, the VOC emissions of six industrial hemp (Cannabis sativa L.) cultivars grown in New Zealand: CFX-2, CRS-1, Ferimon 12, Katani, Futura 75, and Finola. Volatiles emitted from flowers and foliage of eight-week-old plants were collected using a dynamic headspace sampling method and analysed using gas chromatography coupled to mass spectrometry. We assessed the effect of cultivar, sex (monoecious, male, and female), and site (i.e., two sites differing in soil types, maintained under irrigation and rain-fed conditions) on VOC emissions. Thirty-five volatile compounds were tentatively identified from the headspace samples of hemp plants, but none of the cultivars emitted all 35 compounds. β-Myrcene was the most abundant compound in most cultivars. Overall, there was a significant effect of sex, and the interaction of sex and cultivar on the volatile profiles, but no effect of site. Female plants typically emitted more volatiles than their male counterparts and monoecious cultivars. The main compounds driving the difference between cultivars and sexes were (Z)- and (E)-β-ocimene. We hypothesize that differences in emission emerged as a defence strategy to protect costly female flowers from herbivores (since C. sativa is wind pollinated), but this hypothesis needs further testing. We recommend additional studies exploring how biotic and abiotic factors influence hemp VOC emissions, changes in VOCs throughout the crop cycle, the role of VOCs in plant-insect interactions and their use in pest management.
CAUL read and publish agreement 2022
Keywords: 0502 Environmental Science and Management; 0703 Crop and Pasture Production